2011
DOI: 10.1159/000324600
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Vitamin D Status and Cardio-Metabolic Risk Factors in Young European Adults

Abstract: Background/Aims: To explore associations between vitamin D and cardiovascular disease risk factors in young European adults. Methods: This was a cross-sectional analysis of serum 25-hydroxyvitamin D [s25(OH)D], intact parathyroid hormone (iPTH) and biomarkers of cardiovascular disease risk in 195 healthy 20- to 40-year-olds (109 women) with a BMI between 27.5 and 32.5 from Iceland (64°N; n = 82), Ireland (51°N; n = 37) and Spain (42°N; n = 76) during mid-late winter. Results: The median s25(OH)D was 52.8 nmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 80 publications
2
24
0
Order By: Relevance
“…Although vitamin D is not included among antioxidant vitamins, it has been shown from research studies carried out in different countries that vitamin D has an impact on the components of MS and its concentration in patients with metabolic disorders is significantly lower than in healthy individuals. 4,10 In our study, we attempted to assess the risk of deficiency of these vitamins in patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Although vitamin D is not included among antioxidant vitamins, it has been shown from research studies carried out in different countries that vitamin D has an impact on the components of MS and its concentration in patients with metabolic disorders is significantly lower than in healthy individuals. 4,10 In our study, we attempted to assess the risk of deficiency of these vitamins in patients with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced serum triglyceride levels were observed in those living closer to the equator (Spain) compared to more northerly populations in Iceland and Ireland who participated in a weight loss dietary intervention study. 71 The incidence of diabetes (mainly type-2) was affected by latitude in Canadian Inuit indigenous people, with the incidence decreasing with increasing latitude north of the equator 72 in a direction opposite to that observed by a previous study 71 . Further studies are required to examine the nature of the relationships between latitude and obesity, type-2 diabetes and metabolic syndrome.…”
Section: Latitude Gradientsmentioning
confidence: 65%
“…It was noticed that few studies worldwide have focused on the association between vitamin D status and blood lipids in general, especially high cholesterol levels, even though they are the major risk factors for CHD [44]. Some studies reported significant association between low serum vitamin D levels and high triglycerides [33,45,46], but not with hypercholesterolemia. The possible explanation for our results is that all subjects in the current study were hospital-based patients; thus, if they have been clinically diagnosed with hypertension and hypercholesterolemia, they would be on medication for those conditions.…”
Section: Discussionmentioning
confidence: 99%